2019
DOI: 10.1186/s12948-019-0113-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive therapy with rituximab in common variable immunodeficiency

Abstract: Common variable immunodeficiency (CVID) is the most frequent symptomatic primary antibody deficiency in adulthood and is characterized by the marked reduction of IgG and IgA serum levels. Thanks to the successful use of polyvalent immunoglobulin replacement therapy to treat and prevent recurrent infections, non-infectious complications, including autoimmunity, polyclonal lymphoproliferation and malignancies, have progressively become the major cause of morbidity and mortality in CVID patients. The management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 122 publications
0
26
0
2
Order By: Relevance
“…4,31,[39][40][41] In case reports or studies of small numbers of patients with GLILD, corticosteroids, TNF-a inhibitors, MMF, sirolimus, cyclosporin, rituximab monotherapy, abatacept, and immunoglobulin replacement therapy have all been reported to improve GLILD. 3,[42][43][44][45][46][47][48][49][50] In our cohort, we found that a minimum of 6 months of immunoglobulin replacement therapy did not result in improvement of GLILD. Corticosteroid therapy, which is the most commonly used and recommended first-line therapy, 51 was used in 20 of our patients (51%) before referral to our center and was ineffective in treating GLILD.…”
Section: Discussionmentioning
confidence: 52%
“…4,31,[39][40][41] In case reports or studies of small numbers of patients with GLILD, corticosteroids, TNF-a inhibitors, MMF, sirolimus, cyclosporin, rituximab monotherapy, abatacept, and immunoglobulin replacement therapy have all been reported to improve GLILD. 3,[42][43][44][45][46][47][48][49][50] In our cohort, we found that a minimum of 6 months of immunoglobulin replacement therapy did not result in improvement of GLILD. Corticosteroid therapy, which is the most commonly used and recommended first-line therapy, 51 was used in 20 of our patients (51%) before referral to our center and was ineffective in treating GLILD.…”
Section: Discussionmentioning
confidence: 52%
“…Corticosteroids are often used firstline, however, response may be short-lived or incomplete, there are significant side effects associated with protracted use and a proportion of patients are refractory (16,34,36,39). Success with Rituximab, both in combination with azathioprine or mycophenolate mofetil, and as monotherapy, has been reported although controlled trials and long-term outcome data are lacking (40)(41)(42)(43). Elevated levels of B-cell activating factor (BAFF), a cytokine that promotes the maturation and survival of B-cells, within the serum and lungs of patients with CVID-related ILD levels drives B-cell hyperplasia and may account for disease progression in a small proportion of patients (15) with invasive B cells in inappropriate germinal centers (28,44).…”
Section: Interstitial Lung Disease In Common Variable Immune Deficienmentioning
confidence: 99%
“…For genetically undefined CVID, the use of rituximab for autoimmune cytopenias in CVID is one of the most efficacious and safe treatments. Its use was first documented in 2004 (108), and its efficacy and safety have been wellestablished, especially for ITP (109). While ritixumab's efficacy with autoimmune cytopenias may be in part due to its B-cell depleting properties resulting in depletion of autoantibodies, it is thought that its success in CVID patients is also partially due to its effect on T cells (110), again highlighting the importance of T cell abnormalities in CVID.…”
Section: Treatment Of Autoimmunity In Cvidmentioning
confidence: 99%